Inhibitory effect of licorice extract on the germination and outgrowth of Paraclostridium bifermentans spores - Song, Mengmeng; Lei, Yang; Ali, Ahtisham; Xu, Yan; Sheng, Kairan; Huang, Tianran; Huang, Jichao; Huang, Ming (Frontiers in Microbiology, 2022)
The Paraclostridium bifermentans was isolated from the vacuum-packaged chicken and deserved attention for its spoilage properties in vacuum-packaged meat. Therefore, the inhibitory effects of licorice extract on the germination and outgrowth of P. bifermentans spores were investigated, as well as the key bioactive components in the licorice extract involved in inhibiting spore activity in this study. The spores induced by combination-nutrient-germinant (150 mmol/L L-alanine and 20 mmol/L inosine, co-AI) did not germinate when the concentration of licorice extract was ≥ 3.13 mg/mL. And the germination of P. bifermentans spores induced by non-nutrient-germinant (8 mmol/L dipicolinic acid, DPA) was completely prevented by licorice extract at least 1.56 mg/mL. While, the outgrowth of P. bifermentans spores was inhibited at concentration of 0.39 mg/mL. Licorice extract did not seem to damage the non-germinated spores but blocked the germinant sensing. And licorice extract prevented the outgrowing spores from becoming vegetable cells by disrupting the inner membrane. Furthermore, the results obtained from LC-MS data analysis exhibited 15 key bioactive compounds in licorice extract, such as glycyrrhizic acid, liquiritin, etc. Among them, glycyrrhizic acid and liquiritin apioside exerted efficient inhibitory properties on the germination and outgrowth of P. bifermentans spores. This present study provides a baseline to the better understanding of the potential application of licorice extracts to control the P. bifermentans spores in meat products.